(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2019)
Multi-point forming (MPF) is a new flexible forming technology in which the fixed shape of conventional dies is replaced by a pair of opposed matrices of movable punch elements called "punch group".By using multi-point die a variety of three dimensional sheet parts of different shapes can be produced. However due to the discrete contacts between the work piece and punches the dimple defects occurred. In this paper, B-spline technique was used to represent the profile of the final product shape by adjusting the punch height of reconfigurable die. Finite element code (ANSYS 11) was used to simulate the MPF process and to investigate the influence of punch tip radius the interpolator type on the stress distribution, thickness variation and dimpling defect .The simulation results show that the large tip radius and (4mm) rubber interpolator have a great effect in reducing the stress concentration, thickness variation and also prevent the dimpling defect.